Insights about destination brand: Madeira case study - Carvalho, T. F. F.; Sarmento, E. M.; Loureiro, S. M. C. (Tourism and Hospitality International Journal, 2017)
The concept of brand as known today is passed through various (re) definitions over the years. Initially, the brand was associated with house products, but with the evolution of society has come to represent industrial products, people, values, and services. Nowadays due to the great offer of tourist destinations, brands also represent countries, cities, and regions. This type of brands, result from maturation and of the coverage of the functionality of the same. Thus, the tourist brands or place brands, come from the necessity to value the places through its unique characteristics, boosting the visit of tourists and the sustainability of the destination. The island of Madeira is a typical tourist destination, which stands out from the competition through its heritage, in terms of culture and patrimony. With its economy based on tourism and to measure the importance of the Brand, an interview was conducted at one of the main actors in this area, specifically the Regional Tourism Director of the Autonomous Region of Madeira. In addition we have interview 118 tourists during July and August 2017 at Madeira airport.